Modulating electronic structure of metal-organic frameworks by introducing atomically dispersed Ru for efficient hydrogen evolution - Sun, Yamei; Xue, Ziqian; Liu, Qinglin; Jia, Yaling; Li, Yinle; Liu, Kang; Lin, Yiyang; Liu, Min; Li, Guangqin; Su, Cheng-Yong (Nature communications, 2021)
Developing high-performance electrocatalysts toward hydrogen evolution reaction is important for clean and sustainable hydrogen energy, yet still challenging. Herein, we report a single-atom strategy to construct excellent metal-organic frameworks (MOFs) hydrogen evolution reaction electrocatalyst (NiRu 0.13 -BDC) by introducing atomically dispersed Ru. Significantly, the obtained NiRu 0.13 -BDC exhibits outstanding hydrogen evolution activity in all pH, especially with a low overpotential of 36 mV at a current density of 10 mA cm −2 in 1 M phosphate buffered saline solution, which is comparable to commercial Pt/C. X-ray absorption fine structures and the density functional theory calculations reveal that introducing Ru single-atom can modulate electronic structure of metal center in the MOF, leading to the optimization of binding strength for H 2 O and H*, and the enhancement of HER performance. This work establishes single-atom strategy as an efficient approach to modulate electronic structure of MOFs for catalyst design. Developing high-performance, neutral-media H 2 -evolution electrocatalysts is important for clean and sustainable hydrogen energy, yet rare, expensive elements are most active. Here, authors show that metal-organic frameworks modified with single ruthenium atoms as high-performances catalysts.